2012
DOI: 10.1107/s1600536812011518
|View full text |Cite
|
Sign up to set email alerts
|

Cinnarizinium 3,5-dinitrosalicylate

Abstract: The title compound [systematic name: 4-diphenyl­methyl-1-(3-phenylprop-2-en-1-yl)-piperazin-1-ium 2-carb­oxy-4,6-dinitro­pheno­late], C26H29N2 +·C7H3N2O7 −, is the dinitro­salicylate salt of a tertiary amine. Deprotonation of the carb­oxy­lic acid group occurred on the phenolic hy­droxy group. The diaza­cyclo­hexane ring adopts a chair conformation. Intra­molecular O—H⋯O and inter­molecular C—H⋯O and N—H⋯O hydrogen bonds are observed. The N—H⋯O hydrogen bonds are bifurcated at the H atom and connect the cinnar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Cinnarizine can be used in scuba divers without an increased risk of central nervous system oxygen toxicity. The crystal structures of some related compounds viz., cinnarizine (Mouillé et al, 1975), cyclizine hydrochloride (Bertolasi et al, 1980), cinnarizinium dipicrate (Jasinski et al, 2011), cinnarizinium 3,5-dinitrosalicylate (Dayananda et al, 2012), cinnarizinium picrate (Song et al, 2012), have been reported. In view of the importance of cinnarizine, this paper reports the crystal structure of the title compound, C 26 H 30 N 2+ .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cinnarizine can be used in scuba divers without an increased risk of central nervous system oxygen toxicity. The crystal structures of some related compounds viz., cinnarizine (Mouillé et al, 1975), cyclizine hydrochloride (Bertolasi et al, 1980), cinnarizinium dipicrate (Jasinski et al, 2011), cinnarizinium 3,5-dinitrosalicylate (Dayananda et al, 2012), cinnarizinium picrate (Song et al, 2012), have been reported. In view of the importance of cinnarizine, this paper reports the crystal structure of the title compound, C 26 H 30 N 2+ .…”
Section: Methodsmentioning
confidence: 99%
“…For cinnarizine in allergic disorders, see: Barrett & Zolov (1960). For related structures, see: Bertolasi et al (1980); Dayananda et al (2012); Jasinski et al (2011); Mouillé et al (1975); Smith et al (2001); Song et al (2012). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…For the use of the piperazine moiety in the construction of bioactive molecules, see: Choudhary et al (2006). For a related structure, see: Dayananda et al (2012). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…For cinnarizine as a calcium channel blocker, see: Terland & Flatmark (1999), as a nootropic drug, see: Towse (1980) and for a clinical evaluation in various allergic disorders, see: Barrett & Zolov (1960). For related structures, see: Bertolasi et al (1980); Dayananda et al (2012); Jasinski et al (2011); Mouillé et al (1975); Siddegowda et al (2011); Song et al (2012). For puckering parameters, see: Cremer & Pople (1975).…”
Section: Related Literaturementioning
confidence: 99%
“…Cinnarizine can be used in scuba divers without an increased risk of central nervous system oxygen toxicity. The crystal structures of some related compounds viz., cinnarizine (Mouillé et al, 1975), cyclizine hydrochloride (Bertolasi et al, 1980), cinnarizinium dipicrate (Jasinski et al, 2011), cinnarizinium picrate (Song et al, 2012), opipramolium fumarate (Siddegowda et al, 2011) and cinnarizinium 3,5-dinitrosalicylate (Dayananda et al, 2012) have been reported. In continuation of our work on the salts of pharmaceutical compounds and in view of the importance of cinnarizine, this paper reports the crystal structure of the title salt, C 26 H 29 N 2 + .…”
Section: S1 Commentmentioning
confidence: 99%